Comparison of reduction methods in intramedullary nailing of subtrochanteric femoral fractures - Seyhan, Mustafa; Unay, Koray; Sener, Nadir (TURKISH ASSOC ORTHOPAEDICS TRAUMATOLOGY, 2012)
Objective: The aim of this study was to compare the outcomes of three reduction methods used during intramedullary nailing of the subtrochanteric femur fractures. Methods: This study included 45 patients with subtrochanteric femur fractures who were treated with intramedullary nailing. Twenty-two patients underwent clamp-assisted reduction, 11 reduction with cable cerclage, and 12 with blocking screws. Reduction techniques were compared with respect to the early postoperative alignment, one year postoperative alignment, time to full weight-bearing, time to union, Harris hip score at one year, operation and fluoroscopy times, blood transfusion amount, complications, and additional interventions. Results: The clamp-assisted reduction group had a statistically high mean time to full weight-bearing (p=0.038) and a low mean Harris hip score at one year (p=0.002). The blocking screw group's operation times and fluoroscopy times were statistically long. There was no statistically significant difference between the clamp-assisted reduction and cable cerclage groups in terms of operation times and fluoroscopy times. On the other hand, there were statistically significant differences between the clamp-assisted reduction and blocking screw groups (p=0.0001 and p=0.0001, respectively) and between the cable cerclage and blocking screw groups (p=0.037 p=0.0001, respectively) in terms of operation times and fluoroscopy times. There was no statistically significant difference between the clamp-assisted reduction, cable cerclage and the blocking screw groups in terms of early postoperative alignment, one year postoperative alignment, time to union, complications or additional interventions. Conclusion: Clamp-assisted reduction leads to a longer time to weight-bearing and a poorer functional status at one year. Operation time and fluoroscopy time were longest in the blocking screw group.
Keywords: Blocking screw; cable cerclage; clamp-assisted reduction; intramedullary nail; subtrochanteric fracture